The contribution of the faculty of engineering in Islamizing engineering studies - Shuriye, Abdi Omar; Ismail, Ahmad Faris (2008)
Islamization as an idea is not a mere process of engagement rather a dynamic and ongoing school of thought; hence, Islamized engineering is a value-laden enterprise and a process reconceptualization. Islamized engineering sciences will generate diverse insights different, to certain a extent, from western conception of engineering. It will connect us to the history of Islamic literature and the salient manifestations of Islamic civilization. This paper aspires to review and evaluate the methodological and epistemological approaches adopted by the Kulliyyah of Engineering in its attempt to infuse Islamic values in the general framework of its activities; from administration to academic and from student's affairs to curriculum development.